Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1111/j.1365-2591.2010.01697.x
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression profiles of the incisor pulp tissue during fluorosis

Abstract: The gene expression levels in rat pulp tissue changed during fluorosis. The gene expression profiles between the fluorotic model and the normal group will help to understand the multiple pathogenic mechanisms for the altered mineralization patterns observed in fluorotic dentine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Although Wurtz et al [20] demonstrated 8 differentially expressed genes in odontoblast culture cells induced by a fluoride at a non-toxic dose (1 mM), these were not detected in genes that were identified in our cell system. Wu et al [21] also reported that 247 genes were 1.5-fold or more differentially expressed after fluoride treatment in rat incisor pulp tissue. Up-regulation of period circadian clock 1 ( Per1 ) and down-regulations of calpastatin ( Cast ) and programmed cell death 4 ( Pdcd4 ) could be detected in ROE2 cells treated with NaF.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although Wurtz et al [20] demonstrated 8 differentially expressed genes in odontoblast culture cells induced by a fluoride at a non-toxic dose (1 mM), these were not detected in genes that were identified in our cell system. Wu et al [21] also reported that 247 genes were 1.5-fold or more differentially expressed after fluoride treatment in rat incisor pulp tissue. Up-regulation of period circadian clock 1 ( Per1 ) and down-regulations of calpastatin ( Cast ) and programmed cell death 4 ( Pdcd4 ) could be detected in ROE2 cells treated with NaF.…”
Section: Discussionmentioning
confidence: 99%
“…Transcript profiling technologies including DNA microarray have made it possible to profile global gene expression patterns associated with different biological responses during chemical and physiological stresses. To date, several studies have utilized this technology for identifying changes in the gene expression of odontoblast culture cells induced by a fluoride at non-toxic doses [20], incisor pulp tissue during fluorosis [21] and the sperm of mice treated with fluoride [22]. Recently, pathway analysis technologies have enabled the mapping of gene expression data into relevant pathway maps on the basis of their functional annotation and known molecular interactions and we have used these in biological experiments [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…From Wu et al . (2010) – ‘Sixteen female wistar rats weighing approximately 100g were obtained from Experimental Animal Center of Guangxi Medical University. This study was approved by the animal care and use committee of Guangxi Medical University.…”
Section: Introductionmentioning
confidence: 99%
“…The following studies were identified for fluoride (Ge et al, 2011;Sun et al, 2011;Wu et al, 2010;Wurtz et al, 2008;Yan et al, 2007). Four used transcriptomics approaches and one proteomics.…”
Section: Hazardmentioning
confidence: 99%